Hadoop high availability through multiple active name nodes - Vijaya Lakshmi, P; V.S Ramesh, K; Likhitha, P; Pranay Kumar, M (International Journal of Engineering and Technology, 2017)
HDFS having only single dynamic name node, if that name node occur hardware or software failure, the entire HDFS model will be inac-tive position until the recovery of name node. So that to reduce that problem the standby name nodes are placed, which they are an inactive position. On failover occur to primary name node all its metadata will transfer to the standby name nodes. After primary name node fails remaining standby nodes elects one of the nodes to take the position of primary name node. But on transferring the metadata to remaining standby name nodes there will be heavy burden to the primary name nodeIn this paper, we proposed a solution to reduce the load on the primary name node by transferring the metadata to remaining standby name nodes. We compress the entire metadata in the primary name node and sent that data into remaining all standby name nodes.